2019
DOI: 10.1097/mrm.0000000000000155
|View full text |Cite
|
Sign up to set email alerts
|

The diabetes pandemic and associated infections: suggestions for clinical microbiology

Abstract: There are 425 million people with diabetes mellitus in the world. By 2045, this figure will grow to over 600 million. Diabetes mellitus is classified among noncommunicable diseases. Evidence points to a key role of microbes in diabetes mellitus, both as infectious agents associated with the diabetic status and as possible causative factors of diabetes mellitus. This review takes into account the different forms of diabetes mellitus, the genetic determinants that predispose to type 1 and type 2 diabetes mellitu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
131
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 127 publications
(135 citation statements)
references
References 186 publications
(171 reference statements)
0
131
0
4
Order By: Relevance
“…Particularly, defective neutrophil recruitment to the sites of infection was reported in animal models of sepsis [86,87]. Clinical studies reported that the incidence of sepsis is increased in diabetic patients [5]. Accordingly, DM is associated with high severity of sepsis, likely due to compromised immune responses, such as adhesion, chemotaxis, phagocytosis, and bacterial killing by immune cells [88].…”
Section: Neutrophil Dysfunction and Sepsismentioning
confidence: 99%
See 3 more Smart Citations
“…Particularly, defective neutrophil recruitment to the sites of infection was reported in animal models of sepsis [86,87]. Clinical studies reported that the incidence of sepsis is increased in diabetic patients [5]. Accordingly, DM is associated with high severity of sepsis, likely due to compromised immune responses, such as adhesion, chemotaxis, phagocytosis, and bacterial killing by immune cells [88].…”
Section: Neutrophil Dysfunction and Sepsismentioning
confidence: 99%
“…Currently, it is known that there are over 425 million people with DM globally. Worryingly, it is estimated that in 2045, this number will grow to over 600 million [5].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The world is facing a major epidemic of DM. According to International Diabetes Federation, there are an estimated 425 million diabetic patients worldwide with 1 in 10 living with diabetes & 1 in 2 remaining undiagnosed [1]. Available reports suggest that all these patients are at risk of developing DFU.…”
Section: Introductionmentioning
confidence: 99%